Characteristics of metastasis and survival between male and female breast cancer with different molecular subtypes: A population‐based observational study. (12th December 2021) - Fang, Wentong; Huang, Yue; Han, Xu; Peng, Jinghui; Zheng, Mingjie
Abstract: Objective: Male breast cancer (BC) is a rare disease, having different clinicopathological features and survival outcomes from female patients. The aim of this research was to, combine with molecular subtypes, analyze the metastatic patterns, and prognosis between male and female patients, and to determine whether the gender was the independent prognostic factor for BC. Methods: Data used in this study were acquired from the SEER database from 2010 to 2016. The clinicopathology features and metastatic patterns were compared by the Chi‐square test and Fisher's exact test. Kaplan–Meier method was performed to compare overall survival (OS) and factors correlated with OS were determined by Cox regression models. Competing risk models were used to ascertain factors related to breast cancer‐specific death (BCSD). Results: Compared with female BC, the incidence of regional LN (HR 1.849, 95% CI 1.674–2.043, p  < 0.001) and distant metastasis (HR 1.421, 95%CI: 1.157–1.744, p  < 0.001) was higher in male BC. For regional LN metastasis, hormone receptor (HoR)−/HER2+ subtype occupied the majority in both male (55.56%) and female (36.86%) groups. For distant metastasis, HoR−/HER2− subtype (21.26%), and HoR−/HER2+ (7.67%) were in major in male and female group separately. Male patients shared similar combinations of metastases with female groups as for single‐site, bi‐site, and tri‐site metastasis. Gender was an independent prognostic factor for OS ( p  < 0.001) but not for BCSD( p  = 0.620). In subgroup of patients with HoR+/HER2−(OS: p  = 0.003; BCSD: p  = 0.606), HoR+/HER2+(OS: p  = 0.003; BCSD: p  = 0.277), regional LN positive(OS: p  = 0.005; BCSD: p  = 0.379), or bone metastasis (OS: p  = 0.030; BCSD: p  = 0.862), the male cohort had poorer OS but similar BCSD with female cohort. Conclusions: Compared with female patients, male BC had different metastasis patterns and prognostic outcomes, and the affection of breast subtypes on metastasis and survivorship was also different. More attention needs to be paid for specific molecular subtype and more personalized therapeutic strategies should be customized while treating male patients. Abstract : Male BC had different metastasis patterns and prognostic outcomes compared with female patients. The affection of breast molecular subtypes on metastasis and survivorship in male and female cohorts was different. More attention needs to be paid for specific molecular subtype and more personalized therapeutic strategies should be customized while treating male patients.